Precipitation evolution, aging strengthening and thermal stability in Al–Fe-Mg-Zr eutectic alloy via laser powder bed fusion - Feng Li; Wei Zhang; Dan Li; Xiao Jia; Bart J. Kooi; Yutao Pei (Virtual and Physical Prototyping)
Conventional precipitation-hardened aluminum alloys experience severe mechanical degradation above 200 °C due to precipitate coarsening and dissolution. This study presents a novel Al–Fe-Mg-Zr eutectic alloy fabricated via laser powder bed fusion, achieving crack-free fabrication with 99.8% relative density, ultrafine grains, and a heterogeneous cellular-lamellar microstructure. Direct aging (400 °C/4 h) enhances yield strength (YS) to 376.1 MPa (72.6% increase) and ultimate tensile strength to 405.8 MPa (30.7% increase) compared to the as-printed condition, while reducing ductility to 11.1%. The strengthening mechanisms arise from grain boundary strengthening, precipitation strengthening via coherent L12-Al3Zr nanoscale dispersoids, dislocation strengthening, and effective load transfer through submicron-scale Al–Fe intermetallic phases. High-temperature tensile testing reveals excellent mechanical stability, retaining a YS of 124 MPa at 350 °C. After prolonged thermal exposure (400 °C/100 h), the alloy maintains good mechanical properties, demonstrating excellent heat resistance due to the low coarsening rate of Al13Fe4 (0.98 nm3/s) and sustained Al3Zr precipitates. The dual-scale strengthening strategy significantly advances developing high-strength and thermally stable Al alloys for high-performance applications.